2021
DOI: 10.1080/14789450.2021.1886929
|View full text |Cite
|
Sign up to set email alerts
|

Progress regarding the context-of-use of tau as biomarker of Alzheimer’s disease and other neurodegenerative diseases

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 199 publications
0
4
0
3
Order By: Relevance
“…Early prediction of the onset of AD is crucially important for timely prevention and early intervention in this disease. However, the current tools that are used for identifying AD pathology pre-mortem, including brain tau and Aβ PET imaging and CSF protein analysis, are expensive, time-consuming and invasive 24,[38][39][40][41][42][43][44][45]55,56 . Although these methods have been used to predict pathology before clinical symptoms have developed, their invasiveness and cost have limited their use to well funded research settings in academic centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early prediction of the onset of AD is crucially important for timely prevention and early intervention in this disease. However, the current tools that are used for identifying AD pathology pre-mortem, including brain tau and Aβ PET imaging and CSF protein analysis, are expensive, time-consuming and invasive 24,[38][39][40][41][42][43][44][45]55,56 . Although these methods have been used to predict pathology before clinical symptoms have developed, their invasiveness and cost have limited their use to well funded research settings in academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…Using our novel assay, we identified TTR, Aβ, tau231 and α-syn as constituents of the aggregates seen in ADTs exposed to sera from patients with AD and MCI. Prior studies have shown that the concentration of a single protein such as Aβ and a tau protein is increased in the CSF or blood in AD 24,[38][39][40][41][42][43][44][45]55,56 . However, it was not clear whether these proteins are present as aggregates in biofluids.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha hallado superposición genética, neuropatológica y clínica entre la demencia frontotemporal (DFT) algunas afasias progresivas primarias (APP), la esclerosis lateral amiotrófica (ELA) y trastornos del movimiento antes considerados parkinsonismos atípicos o parkinsonismos plus (Mark, 2001) como la degeneración corticobasal (DCB) (Rebeiz et al, 1967;Armstrong et al, 2013;Alexander et al, 2014) y la parálisis supranuclear progresiva (PSP) o enfermedad de Steele-Richardson-Olszewski (Steele et al, 1964;Boxer et al, 2017;Höglinger et al, 2017). Esto llevó a la nueva clasificación de estos cuadros como proteinopatías (Bayer, 2015;Campese et al, 2021;Chopra et al, 2022), adscribiendo los mismos a diferentes perfiles genéticos (ver Tabla 1). Todas estas patologías comparten la presentación de compromiso cognitivo, conductual y funcional, muchas veces asociado a trastornos del sistema nervioso autónomo.…”
Section: Trastornos De Conducta Y Psicosis En Neurologíaunclassified
“…Current biomarkers (Aβ, tau, and neurodegeneration) are measured in CSF or by brain neuroimaging. Specific Aβ-PET and tau-PET tracers enable the study of the misfolded and accumulated proteins (but not monomers and oligomers) in the brain in vivo [ 95 , 96 , 97 , 98 , 99 ]. In the brain, Aβ deposition may be monitored by 11 C-Pittsburgh compound B ( 11 C-PiB) or 18 F-florbetapir PET; tau deposition can be monitored using newer 18 F-based tau binding ligands; and neurodegeneration and synaptic damage can be observed via 18 F-fluorodeoxyglucose ( 18 F-FDG) PET or structural magnetic resonance imaging (MRI) data analysis [ 27 , 100 , 101 ].…”
Section: Risk Factors and Biomarkers Of Alzheimer’s Diseasementioning
confidence: 99%